Long-term results and comparison of flow re-direction endoluminal device and pipeline embolization device in endovascular treatment of intracranial carotid aneurysms * - GÜNDOĞMUŞ, CEMAL AYDIN; TÜRELİ, DERYA; BALTACIOĞLU, FEYYAZ; BAYRİ, YAŞAR (SAGE PUBLICATIONS INC, 2022)
Objective This study aims to compare the efficacy, safety, and long-term outcomes of two flow diverters, i.e., pipeline embolization device and flow re-direction endoluminal device, in the treatment of distal carotid aneurysms. Methods A total of 138 patients with 175 aneurysms were included from February 2012 to September 2019. Ninety-nine aneurysms were treated with flow re-direction endoluminal device and 76 with pipeline embolization device. Angiographic follow-ups were at the 6th, 12th, 24th, 36th, and 60th months; the O'Kelly-Marotta grading scale was used to assess aneurysms occlusion. Outcomes of two devices were compared; possible associations regarding patient characteristics, aneurysm properties, treatment details, and adverse events were evaluated. Results The mean follow-up period was 33 months, with 10 patients lost to follow-up. Occlusion rates at the 6th and 12th months and during the last follow-up were similar for flow re-direction endoluminal device (81%, 84%, and 90%) and pipeline embolization device (82%, 85%, and 93%). Occlusion rates were also similar after stand-alone use without coiling. There was no significant difference regarding adverse event rates with a 10.9% overall complication rate, 3.6% mortality, and 0.7% permanent morbidity. All the mortality and morbidity were related to hemorrhagic complications. Device deployment failure was observed with five flow re-direction endoluminal devices and two pipeline embolization devices, whereas two severe in-stent stenoses occurred with each device. Conclusions Both flow re-direction endoluminal device and pipeline embolization device are feasible and effective in flow diversion of distal internal carotid artery aneurysms, with similar adverse events rates and aneurysm occlusion success. Aneurysm occlusion rates increase with time, while the presence of an integrated branch significantly decreases treatment success.
Keywords: Aneurysm; flow diverter; flow re-direction endoluminal device; pipeline embolization device; internal carotid artery; FOLLOW-UP; CEREBRAL ANEURYSMS; ARTERY ANEURYSMS; MULTICENTER; EXPERIENCE; DIVERTORS; STENT